IZTEGI - SOLAS "Bocabularioa Ezqueraz Jaquiteco, eta Ezqueraz Verba Eguiteco 1562" - Idoyaga, Sabin (EGAN, 2021)
SABIN IDOYAGA: IZTEGI - SOLAS "Bocabularioa Ezqueraz Jaquiteco, eta Ezqueraz Verba Eguiteco 1562"